2015
DOI: 10.1039/c5ra14890a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ketones via organolithium addition to acid chlorides using continuous flow chemistry

Abstract: An efficient method for the synthesis of ketones using organolithium and acid chlorides under continuous flow conditions has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…Concerning laboratory experiments, many authors successfully synthesized a variety of organolithium compounds within microstructured devices, by taking advantage of precisely adjustable reaction conditions to easily control those highly exothermic and fast reactions [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Key examples are studies by the groups of Yoshida, Feng, and Browne, as shown below.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning laboratory experiments, many authors successfully synthesized a variety of organolithium compounds within microstructured devices, by taking advantage of precisely adjustable reaction conditions to easily control those highly exothermic and fast reactions [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Key examples are studies by the groups of Yoshida, Feng, and Browne, as shown below.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] Recently, the Jamison group described an efficient continuous ow synthesis of ketones from carbon dioxide and organolithium or Grignard reagents at ambient temperature and pressure. 39 The Kim group developed an efficient method for the synthesis of ketones using organolithium reagents and acid chlorides under continuous ow conditions at À40 C. 40 Unfortunately, most of the solvents used in the synthesis of diaryl ketones are not environmentally friendly. In recent years there has been a trend towards the use of bio-derived, green solvents as replacements for hazardous and/or environmentally-damaging solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The flow process could be efficiently applied to aryllithiums, alkenyllithiums as well as alkynyllithiums. In a similar way, Kim developed the synthesis of ketones by a continuous flow addition of organolithiums to acylchlorides (Scheme b) . In both processes, the high level of chemocontrol, with respect to batch processing, is a consequence of the accurate control of the reaction parameters applied in the flow microreactor systems.…”
Section: Taming Short‐lived Organolithiums In Flowmentioning
confidence: 99%
“…In as imilar way,K im developed the synthesis of ketones by ac ontinuous flow addition of organolithiumst oa cylchlorides (Scheme 12 b). [34] In both processes, the high level of chemocontrol, with respectt ob atch processing, is ac onsequence of the accurate controlo ft he reaction parameters appliedi nt he flow microreactor systems. It is worth mentioning that the formation of the tertiarya lcohol is very difficult to controlu nder batch conditions, even if the reaction is performed at very low temperature.…”
Section: Taming Short-lived Organolithiums In Flowmentioning
confidence: 99%